P744 Safety of live vaccines in children exposed to biological agents for inflammatory bowel disease (IBD) in utero or during breastfeeding. (30th January 2023) - Chaparro, M; García Donday, M; Rubio, S; Calviño Suarez, C; Nuñez Ortiz, A; Figueira, M; Marín Pedrosa, S; Rivero, M; Fernández-Clotet, A; Madero, L; Diz-Lois Palomares, M T; Pérez-Martínez, I; et al.
Abstract: Background: Biological drugs used for IBD are detected in breast milk at a concentration below 10% of the maternal serum concentration and have therefore been considered as permitted drugs. However, warnings have recently been published regarding vaccination with live agents in children whose mothers receive infliximab during breastfeeding. Aim: To assess the risk of serious adverse events related to the administration of live vaccines in children exposed to biological drugs in utero or whose mothers were receiving biological agents during breastfeeding. Methods: Children born to IBD mothers from DUMBO registry of GETECCU were included. DUMBO is a prospective, observational and multicentre registry, which enrolls pregnant women with IBD over 5 years in 70 centres in Spain. Data on treatment during gestation, type of lactation, breastfeeding, end-date of breastfeeding, maternal treatments during breastfeeding and serious adverse events in children from birth are being prospectively included contacting with the mothers every-3-months. Following the Spanish immunization calendar, rotavirus vaccine is (voluntarily) administered at 2, 4 and 6 (3 rd dose only with Rotateq ® ) months; measles, mumps and rubella (MMR) at 12 months and 3-4 years of age; and varicella at 15 months and 3-4 years of age. Results: 526 newborns were included in the registry at the time of data analysis. A total of 205 (39%) had been exposed to biologics during pregnancy or breastfeeding (table 1): 80 (42%) during pregnancy, 7 (2%) during breastfeeding, and 109 (57%) during both. Newborn's demographics and exposure to drugs during breastfeeding are summarized in table 2. Mean follow-up was 12 months; proportion of children breastfed during follow-up is shown in table 3a. The percentage of children who had been vaccinated according to the recommended schedule was above 95% at all visits (table 3b). Live vaccines administered to children exposed in utero to biologics during the 3 rd trimester of gestation are shown in table 4a. From birth, 71% of infants were breastfed (52% exclusively breastfed). Live vaccines administered to children breastfed at least until month 6, until month 12 and until month 15 are summarized in table 4b. No serious adverse event related to live vaccine was reported in our cohort. Conclusion: Administration of live virus vaccines from 12 months of age in children born to IBD mothers and exposed to biological drugs in utero or during breastfeeding seems safe and should not be recommended against vaccination or breastfeeding. Rotavirus vaccine (under 6 months of age) appears to be equally safe in these children.